Gradual increase in the risk of match injury in Norwegian male professional football: A 6-year prospective study - Bjørneboe, J.; Bahr, R.; Andersen, T. E. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The aim of this study was to monitor injury incidence and pattern in Norwegian male professional football over six consecutive seasons and compare the risk of injury between the preseason and competitive season. All time loss injuries were recorded by the medical staff of each club. In total, 2365 injuries were recorded. The incidence of acute injuries was 15.9/1000 match hours [95% confidence interval (CI): 14.9-16.8], 1.9/1000 training hours (95% CI: 1.7-2.0), and 1.4 (95% CI: 1.3-1.5) overuse injuries/1000 h. A linear regression model found an annual increase of 1.06 acute match injuries/1000 h (95% CI: 0.40-1.73), corresponding to a total increase of 49% during the 6-year study period. When accounting for interteam variation and clustering effects using a general estimating equation model, the increase in injury incidence was 0.92 (95% CI: -0.11-1.95, P = 0.083). No difference in the risk of acute match injuries (rate ratio (RR): 0.86, 95% CI: 0.73-1.01), acute training injuries (RR: 1.16, 95% CI: 0.99-1.36), or overuse injuries (RR: 1.04, 95% CI: 0.89-1.21) was observed between the preseason and competitive season. In conclusion, the overall risk of acute match injuries in Norwegian male professional football increased by 49% during the study period, although this increase was not fully consistent across teams. We detected no change in the risk of training and overuse injuries or any difference between the preseason and competitive season.